The Best Location of Belt Truss System in Tall Buildings Using Multiple Criteria Subjected to Blast Loading - Reihaneh Tavakoli; Reza Kamgar; Reza Rahgozar (Salehan Institute of Higher Education, 2018)
The main goal of this paper is to investigate the effect of blast phenomenon on structures to determine the best location of belt truss system in tall buildings. For this purpose, one of the exterior frames of a tall steel building, in which the belt truss is located, is considered. The steel frame model is subjected to two different charges of equivalent weight which are applied in two different standoff distances. In this research, the best location of the belt truss system is determined using OpenSees software based on the nonlinear dynamic analysis. The best location of the belt truss system for different types of loading is investigated both with and without considering the post-buckling effect for all members of the belt truss system. The results show that when blast charges are located in a 5-meter range from the building (R=5), post buckling effect of truss elements are more obvious than the case in which blast charges are located in a 10-meter range (R=10); this, in turn, causes the amount of base moment to be completely different when the belt truss is located in the first storey in comparison to the cases where the belt truss is located in any other stories. In addition, if the explosion occurs near the building when the base moment is considered as a criterion, the post buckling effect has a significant role.